The Effect of Financial Performance on Company Value Moderated by Dividend Policy - Annisa Nurul Lita; Mursidi Mursidi; Fika Fitriasari (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2022)
The purpose of this study was to determine and analyze the effect of financial performance on firm value with dividend policy as a moderating variable. The object of this research is automotive and component companies listed on the Indonesia Stock Exchange in 2016-2020. The type of research used is quantitative research. The sampling technique in this study used a purposive sampling method with a total sample of 11 companies. The data analysis technique used multiple linear regression analysis using IBM SPSS Statistics v20 softwer. The results showed that there was a positive and significant effect of financial performance as a proxy for ROA and ROE on firm value. Dividend policy is not able to strengthen the relationship between financial performance and firm value.